Why FIRREA and Civil Enforcement Cannot Replace Individual Criminal Liability - Timothy Ly (Washington University Journal of Law & Policy, 2016)
This Note addresses the high burden of proving specific criminal intent within the context of the 2008 financial crisis. Ly analyzes the Department of Justice’s use of civil penalties under the Financial Institutions Reform, Recovery, and Enforcement Act (FIRREA) and addresses their impact on deterring illegal behavior. Ly argues that FIRREA has failed to adequately deter illegal behavior and proposes a financial mismanagement law that would lower the criminal burden from specific intent to recklessness.
Keywords: Civil penalties; U.S. ex rel. O’Donnell v. Bank of America Corp et al; U.S. v. Wells Fargo Bank; N.A.; United States v. The Bank of New York Mellon; Corporate executives; Criminal fraud; Financial Crisis; Department of Justice; Financial Institutions Reform; Recovery; and Enforcement Act; FIRREA